Research progress on skin photoaging and oxidative stress - Chen, Xi; Yang, Chunsheng; Jiang, Guan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Skin photoaging, which is a kind of exogenous aging, refers to skin elasticity degradation, skin roughening, and wrinkle formation processes because of cascading reactions of a series of kinases after growth factor receptors and cytokine receptors are activated on a cell surface under the UV effect. An extensively recognized skin photoaging mechanism is free radical–oxidative stress concept, proposed by Sohal who represents the authority of the US aging studies. Over the past decade, many new developments in the oxidative stress mechanism have been achieved in terms of the occurrence, development, prevention, and treatment of photodamage.